P59 TLR4 antagonist in acute liver failure: a novel therapeutic strategy. (16th November 2010) - Shah, N; Dhar, D; Montes de Oca, M; Jover-Cobos, M; Davies, N; Mohamed, F; Mookerjee, R P; Jalan, R
Abstract : Introduction: Acetaminophen (APAP) toxicity is the commonest cause of acute liver failure (ALF) which is characterised by multiorgan failure manifested by rapid acute liver injury, severe brain oedema and renal failure. Without liver transplantation, about 40% patients die and its treatment is an unmet medical need. Unregulated inflammatory response plays an important role in its pathogenesis. A multitude of cytokines are released during ALF with consequent activation of NfKB and progressive liver injury. We hypothesised that Toll-like receptor-4 may be critical in the progression to multiorgan failure. Aim: The aim of this study was to determine whether administration a novel TLR4 antagonist (STM28) to an APAP model of ALF in mice would prevent liver injury and its deleterious effect on the brain and the kidneys. (STM28 was kindly gifted by Professor Ken-ichi Tanamoto, Division of Microbilogy, National Institute of Health Sciences, Tokyo 158-8501, Japan). Method: Three groups of Cd1 male mice were studied. Sham, APAP (acetaminophen, 500 mg/kg single dose IP after over night fasting), APAP+TLR4 antagonist (STM28; 20 ug IP, 1 h prior to the administration of APAP and 6 h later). All the mice were hydrated, administered 10% dextrose and kept in temperature controlled environment. Blood was collected for biochemistry and cytokine assay. Liver, kidney and brain were collected for western blotting and cytokine analyses and the brain frontal cortex for brain water. Animals were sacrificed at 12 h after APAP administration. Results: Administration of APAP led to an increase in the level of liver enzymes, ALT (p=0.004) and AST (p=0.007) in comparison to the Shams, which was significantly reduced (ALT (p=0.01) and AST (p=0.008)) in the TLR4 antagonist group. ALF associated increase in ammonia (p=0.001) and brain water (p=0.04) were significantly reduced (ammonia (p=0.03); brain water (p=0.05)). ALF associated renal failure (p=0.004) was also markedly attenuated (p<0.09). Protein expression of NFkBp65 on western blot showed an increased expression in brain and kidney (p=0.03) and (p=0.02) respectively which was reduced to values that were not significantly different to Sham levels (brain (p=0.04) and kidney (p=0.02)). The expression of NFkBp65 protein expression on western blot in liver was down-regulated in ALF compared with sham (p=0.01) animals and restored in TLR4 antagonist group Sham values (p=0.02). Conclusion: The results of this study show for the first time a role for TLR4 in pathogenesis of multiorgan failure in ALF. The data strongly support a potential therapeutic role for TLR4 antagonist in the prevention of progression of ALF.